2014
DOI: 10.1093/bja/aet407
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of immediate postoperative pain using the analgesia/nociception index: a prospective observational study

Abstract: ClinicalTrials.gov NCT01796249.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
150
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(157 citation statements)
references
References 33 publications
2
150
0
5
Order By: Relevance
“…We first conducted studies on the measurement of HRV in adults under general anesthesia [22] . One study found that our method had a low sensitivity and specificity for postoperative acute-pain evaluation [26] ; yet, a majority of data indicate that our technology allows anesthetists to adapt analgesia during surgical procedures, labor, and postoperative recovery time [22-24, 26, 35] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We first conducted studies on the measurement of HRV in adults under general anesthesia [22] . One study found that our method had a low sensitivity and specificity for postoperative acute-pain evaluation [26] ; yet, a majority of data indicate that our technology allows anesthetists to adapt analgesia during surgical procedures, labor, and postoperative recovery time [22-24, 26, 35] .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated the ability of our index to investigate the autonomic response to painful stimuli in adults (both conscious and unconscious) [22][23][24][25][26] . We have also demonstrated that our method can be used to assess pain and discomfort in newborn and preterm infants [27] .…”
Section: Introductionmentioning
confidence: 99%
“…Biz de verilerimizi diğer yayınlarla karşılaştırabilmek amacıyla aynı değerleri eşik değer olarak kabul ettik. Ayrıca ANİ'nin sadece hemodinamik istenmeyen olayların erken saptanması dışında postoperatif ağrı yönetiminde de kullanılabileceğine ve ANİ değerleriyle postoperatif ağrı şiddetinin ön görülebileceğine dair yayınlar da vardır (9,32). Bilindiği üzere ameliyat sonrası oluşan ağrı operasyonun büyüklüğü ile paralel değildir.…”
Section: Discussionunclassified
“…In two studies conducted in the PACU, patients who had undergone surgery under general anesthesia had their ANI monitored prior to extubation. 15,16 It was determined that their ANI correlated negatively with the pain scores on a numeric rating scale (NRS, 0-10 scale) in the PACU. An Australian study 17 monitored the ANI and the NRS pain scores in 120 patients in the PACU after elective surgery and found a weak negative correlation between these two parameters.…”
Section: Résumémentioning
confidence: 99%